Ochrona środowiska w sektorze małych i średnich przedsiębiorstw w świetle planów wykorzystania funduszy strukturalnych UE - Kociszewski, Karol (Environment Protection in the SME Sector in the Light of Plans of the European Union Structural Funds Use, 2005)
The paper describes possibilities of use of the EU structural funds for environment protection measures in the small and medium size enterprises sector. They are included in priorities and measures of the Community support absorption programs. Their effective realization should be one of the most important incentives of economic growth in Poland. Taking into account significant role of small and medium size enterprises in this process, creation of EU projects financing sources is meaningful. Therefore, the policy of banking sector should be intensified. Wide possibilities of environment protection initiatives create a chance to combine the evolution of small and medium size enterprises sector with the implementation of sustainable development. The growth of economic welfare would come together with environment improvement and beneficial changes in society structure (middle class development).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 98-110